2003
DOI: 10.1038/ni946
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 7 and T cell receptor signals regulate homeostasis of CD4 memory cells

Abstract: Immunological memory depends on the long-term maintenance of memory T cells. Although the factors that maintain CD8 T cell memory are well understood, those responsible for CD4 memory are not well defined. We have shown here that interleukin 7 (IL-7) was an important survival factor for CD4 memory T cells that together with T cell receptor (TCR) signals regulated homeostasis of the CD4 memory population in lymphopenic conditions and in the intact immune system. Thus, IL-7 contributes to the maintenance of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
356
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(377 citation statements)
references
References 41 publications
18
356
1
2
Order By: Relevance
“…1). A number of different cytokines, particularly IL-7 and IL-15, have been reported to be required for survival and maintenance of memory T cells in vivo [26,27,29,30]. In our model system, IL-2 is the only exogenously added cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). A number of different cytokines, particularly IL-7 and IL-15, have been reported to be required for survival and maintenance of memory T cells in vivo [26,27,29,30]. In our model system, IL-2 is the only exogenously added cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-7 was also shown to promote homeostatic proliferation in CD8 T cells [29]. Recently, it has been shown that IL-7, but not IL-15, is required for the maintenance of CD4 memory T cells [27,30].…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing concept of how circulating antigen‐experienced T lymphocytes are maintained is that of homeostatic proliferation, driven by cytokines, replacing memory T cells which die either due to a limited intrinsic half‐life, or by neglect, not being able to secure sufficient survival stimuli. The concept has been detailed out in a review by Surh and Sprent,94 summarizing evidence that interleukin‐15 is an essential cytokine for the maintenance of CD8 + memory T cells,95 while maintenance of CD4 + memory T cells is dependent more on IL‐7 than on IL‐15 96, 97. T‐cell receptor signaling seems not to be important for the maintenance of CD4 + memory T cells.…”
Section: The Lifestyle Of Circulating Memory T Lymphocytesmentioning
confidence: 99%
“…IL-2 and IL-15 can also support memory cell division and have been used in combination with Ag-driven stimulation, for the expansion of CTL [24][25][26][27][28][29]. IL-7 regulates peripheral T-cell homeostasis, and contributes to the generation and long-term survival of both CD4 1 and CD8 1 memory T lymphocytes in vivo [30,31]. In some cases IL-7 amplifies Agdriven T-cell responses [32][33][34][35][36], favors the transition of effector to memory cells [31,[37][38][39], and sustains a slow, homeostaticlike, Ag-independent memory T-cell proliferation [24,30,40].…”
mentioning
confidence: 99%
“…IL-7 regulates peripheral T-cell homeostasis, and contributes to the generation and long-term survival of both CD4 1 and CD8 1 memory T lymphocytes in vivo [30,31]. In some cases IL-7 amplifies Agdriven T-cell responses [32][33][34][35][36], favors the transition of effector to memory cells [31,[37][38][39], and sustains a slow, homeostaticlike, Ag-independent memory T-cell proliferation [24,30,40]. Furthermore, its administration at the time of Ag withdrawal supports memory CD8 1 T-cell generation [41], and enhances vaccine-mediated immunity when provided in adjuvant settings [42,43].…”
mentioning
confidence: 99%